Primary epidermoid carcinoma of parotid gland - Keles, E.; Ozercan, I. H.; Karlidag, T.; Kaygusuz, I.; Yalcin, S.; Alpay, H. C.; Sapmaz, E. (Galenos Yayincilik, 2006)
Objectives: To investigate the incidence of primary epidermoid carcinoma of parotid gland among the neoplasms originated from parotid glands, clinical behaviors and treatment results. Methods: Between 1992-2004, the files of 98 patients who were operated due to mass in parotid gland in the Ear Nose Throat Department of Firat Medicine Center of University of Firat researched retrospectively. The patients who had tumours primarily originated from parotid gland were evaluated according to age, sex, symptoms and findings, localization, treatment choosing, follow up time and recurrence. Results: The frequency of primary epidermoid carcinoma of parotid gland among parotid neoplasms was 2% (n=2) in duration of 12 years. Two patients were male and their ages were 64 and 69. The complaint of patients is asymptomatic swelling under of the ear. The localization of tumours was on the tail of parotid gland in both of two patients. No distant metastasis was detected preoperatively. The combination of radical surgery and postoperative radiation therapy were performed as treatment. The diagnosis of primary epidermoid carcinoma of parotid gland was confirmed hispathologically. No distant metastasis or local recurrence were found in postoperative follow up on 29th and 6th month respectively. Conclusion: Primary epidermoid carcinoma of the parotid gland has bad prognosis. combination of early diagnosis wide surgical treatment and postoperative radiation therapy, supply the better cure rates and locoregional control. Despite of patient's number we think that our findings contributed the affirmative knowledge to the literature because of primary epidermoid carcinoma of parotid gland is a very unusual tumour.
Keywords: Parotid gland; primary epidermoid carcinoma